A rare case of de novo 20p12.3 microdeletion syndrome in a nine-year-old female: case report and literature review - Aljedani, Hanan; Faden, Yousef; Alghamdi, Manar; Alzahrani, Alshaimaa; Shawli, Aiman; Albakistani, Reem (Frontiers in Genetics, 2025)
Chromosomal deletion syndromes are common worldwide. However, one rare condition that distinguishes a limited number of reported cases and variable phenotypes is 20p12.3 microdeletion syndrome. This case report describes a nine-year-old girl diagnosed with 20p12.3 microdeletion syndrome. Genetic testing revealed a deletion spanning 3.5 Mb and containing 31 genes. The patient presented with a range of clinical manifestations, including growth faltering, short stature, controlled seizure disorder, dysmorphic features, and metabolic disturbances. Regarding dysmorphic features, she presented with malar hypoplasia, a high arched palate, microstomia, long philtrum, proptosis, and retrognathia. Metabolic disturbances were primarily manifested as episodes of hypoglycemia with a high anion gap metabolic acidosis. Despite receiving growth hormone therapy as management for short stature, the patient exhibited low levels of insulin-like growth factor 1 (IGF1). This case report adds to the limited body of knowledge regarding 20p12.3 microdeletion syndrome.